Potency of Genus Cinnamomum in Addressing Type 2 Diabetes: A Review - Baso Ilham; Ummi Zubaidah, Luhana Ahadia (Proceeding International Conference on Religion, Science and Education, 2023)
Nowadays, type 2 Diabetes Mellitus (T2DM) is denoted as prominent metabolic disorders worldwide and rank 6th of disease-associated death in Indonesia. Current T2DM medications are vary with their own benefits and drawbacks. The use of medicinal plants have their corridor in the treatment of diabetes because of significant results with less side effects compared to other medication. Among many herbs, genus Cinnamomum from Lauraceae family has broadly used as folklore medicine against chronic ailment like diabetes. This paper will review scientific finding related to potency of genus Cinnamomum as anti-T2DM. All data are obtained from ScienceDirect, Springer, PubMed, ResearchGate and Google Scholar that published in the last 20 years. At the beginning, the paper will indicate species of Cinnamomum which often studied for antidiabetic. Subsequently, each species will be identified phytochemistry which is bioactive compound that responsible for antidiabetic. Pharmacological properties comprising bioassay design and elaboration of molecular pathway will be discussed in the last part. This paper is expected to provide a reference for pharmaceutical research and clinical application of this genus in against T2DM.